Efektivitas Sign System Dan Intensitas Informasi Petunjuk Arah Sebagai Media Komunikasi Visual Kota Lama Semarang - Muhamad Hasan Basori; Mukaromah Mukaromah; Muhammad Noor Hidayat (Universitas Bumigora, 2022)
The city of Semarang has excellent tourist destinations and its own characteristics that become its strengths, namely the Old City History Tour which utilizes buildings from the Dutch colonial era in Semarang City. To support Semarang City tourism known by tourists, an effective and communicative information media is needed so that visitors know the identity of an object, signs and directions to the next destination, one of which is the use of a media sign system. This study aims to examine how effective the use of the sign system and the intensity of information instructions that have been applied to tourist areas around the Kota Lama Semarang are by using the Direct Rating Method (DRM), through a quantitative research method approach. The variables used are the effectiveness of the sign system, the intensity of directions and visual communication media. The results of the research that were processed by 100 respondents were that there was no relationship between the effectiveness of the sign system and information on directions in the Kota Lama Semarang, there was no relationship between the effectiveness of the sign system and the visual communication media in the Kota Lama Semarang, there was no relationship between the information instructions directions with visual communication media in the Kota Lama Semarang. These three results mean that the three variables are not related to each other, this could be because the sign system in the Old City of Semarang is not functioning as it should, because it should be a sign system that can provide good information to visitors and have attractive visuals. , but in reality this is not the case, namely that the sign system in the city of Semarang does not or does not provide information to visitors and also the sign system does not have good visuals so that it is less able to attract visitors in the Kota Lama Semarang.